Prevalence of Obesity and Anemia Among Early Adolescents in Junior Secondary Schools: A Cross‐Sectional Study in Ouagadougou, Burkina Faso. (21st August 2022) - Mank, Isabel; De Neve, Jan‐Walter; Mauti, Joy; Gyengani, Guillaume A.; Somé, Paul‐André; Shinde, Sachin; Fawzi, Wafaie; Bärnighausen, Till; Vandormael, Alain
ABSTRACT: BACKGROUND: The school presents an ideal environment to positively impact the long‐term health and nutrition outcomes of early adolescents, who are at risk of obesity and anemia. METHODS: In this cross‐sectional survey, we described differences in weight and anemia by sociodemographic, diet and physical activity indicators among 1059 students aged 11 to 15 years from 22 junior secondary schools in Ouagadougou, Burkina Faso. Weight was based on body mass index (BMI) z‐scores according to the WHO reference and anemia status was defined by standardized hemoglobin (Hb) measure cut‐offs. We calculated dietary diversity scores (DDS) from a 24‐hour dietary recall and a global diet quality score (GDQS) from a 7‐day dietary recall. RESULTS: The prevalence of obesity (5%) and anemia (50%) was relatively high among the students, which differed significantly between gender, household wealth and school grade, but not age groups. Eighteen percent of the female adolescents were overweight or obese and 22% were moderately anemic compared to 13% and 16% of the male adolescents. Dietary diversity was significantly different between weight categories, but not anemia status. For physical activity, those taking transportation to school were significantly more likely to be overweight or obese. In adjusted multivariable Poisson regression analyses, only the DDS was significantly associated with thinness and both thinness and anemia, while taking transportation to school was significantly associated with overweight among adolescents. CONCLUSION: We encourage the promotion of school‐based interventions and provision of a curriculum on health and healthy eating in order to reduce obesity, anemia, and its comorbidities.